Effectiveness of reducing ammonia levels in medical waste using a combination of palm fiber bio adsorbent and nanofiltration membrane - Ulfah Dwijayanty; Subriyer Nasir; Novia Novia (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
In this study, the management of domestic wastewater from the regional hospital of Ogan ilirdistrict was carried out by combining adsorption methods using palm fiber activated charcoaladsorbent and filtration using nanofiltration (NF) membranes. The palm fiber activated charcoaladsorbent was produced through a combustion process at 100 ºC for ±24 hours which resultedin a moisture content and ash content of 1.179 and 4.012 %, respectively. Palm fiber charcoalwas activated using sulfuric acid (H2SO4) and then analyzed using Scanning ElectronMicroscope-Energy Dispersive X-Ray (SEM-EDX). The hospital domestic waste treatmentprocess was carried out with variations in operating time of 20, 40, 60, 80, 100 minutes andflow rates of 2 and 3 L/min which were then analyzed for ammonia levels before and after themanagement process.